Biodiversity patterns of small mammals and their natural predators: implications for rodent pest management in agricultural systems - Christopher I. Imakando; G. Mandela Fernández-Grandon; Grant R. Singleton; Steven R. Belmain (Journal of Pest Science, 2026)
There is increased interest in replacing the use of rodenticides with ecologically based rodent management practices to control rodent pests in agricultural ecosystems. One of the suggested methods is biological control by natural predators such as meso-carnivores and raptors. However, meso-carnivores and raptors, like other predators inhabiting agricultural ecosystems, face many threats, including persecution and habitat loss. These threats influence the distribution, habitat use and ecosystem service of meso-carnivores and raptors. Little is known about the extent to which meso-carnivores and raptors can regulate rodent pest populations and thereby reduce damage to agricultural crops. The aim of this study was to assess the diversity and abundance of small mammals (rodents and shrews) and their natural predators (meso-carnivores and raptors) in three different habitats (maize fields, forest, and natural grassland). Our results show that habitat had a significant effect on the intensity of use of a habitat by meso-carnivores and raptors, with their intensity of use generally highest in maize fields and lowest in the natural habitat. Also, the higher the number of individuals of small mammals in the habitat, the higher the intensity of use of a habitat by their natural predators. These results highlight the potential of meso-carnivores and raptors in the regulation of rodent pests. We recommend conducting experiments to quantify the impact of meso-carnivores and raptors on rodent pest populations. Evidence-based results on the predation services provided by meso-carnivores and raptors in agricultural landscapes will be important in promoting the coexistence between people and meso-carnivores and raptors and harness the full benefits of the potential ecosystem services that they provide.

Indigenous stewardship and co-management in action: a case study on blue carbon from a mangrove ecosystem on the Great Barrier Reef - Micheli D.P. Costa; I. Noyan Yilmaz; Pawel Waryszak; Rory Crofts; Melissa Wartman; Pere Masqué; Brian Singleton; Gavin Singleton; Ashlyn Skeene; Lucy Friend; Peter I. Macreadie (Ocean & Coastal Management, 2026)

Sugar Consumption in Adults and Children: Are There Differences Across Biological Sex or Socioeconomic Status? - C. Fose; L. Jones; I. Mcpherson; A. Singleton (Journal of the Academy of Nutrition and Dietetics, 2023)

Vegetation cover and food availability shapes the foraging activity of rodent pests in and around maize fields - Christopher I. Imakando; G. Mandela Fernández-Grandon; Grant R. Singleton; Steven R. Belmain (Agriculture, Ecosystems & Environment, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Evidence for rapid, tide-related shifts in the microbiome of the coral Coelastrea aspera - M. J. Sweet; B. E. Brown; R. P. Dunne; I. Singleton; M. Bulling (Coral Reefs, 2017)

Avian Urine: Its Potential as a Non-Invasive Biomonitor of Environmental Metal Exposure in Birds - J. B. Clapp; R. M. Bevan; I. Singleton (Water, Air, & Soil Pollution, 2012)

Sodium Application Enhances DDT Transformation in a Long-Term Contaminated Soil - D. Kantachote; I. Singleton; R. Naidu; N. McClure; M. Megharaj (Water, Air, & Soil Pollution, 2004)

Influence of Petroleum Hydrocarbon Contamination on Microalgae and Microbial Activities in a Long-Term Contaminated Soil - M. Megharaj; I. Singleton; N. C. McClure; R. Naidu (Archives of Environmental Contamination and Toxicology, 2000)

Effect of Pentachlorophenol Pollution Towards Microalgae and Microbial Activities in Soil from a Former Timber Processing Facility - M. Megharaj; I. Singleton; N. C. McClure (Bulletin of Environmental Contamination and Toxicology, 1998)